Prophylactic antibiotic use in COPD and the potential anti-inflammatory activities of antibiotics - Huckle, Anthony W.; Fairclough, Lucy C.; Todd, Ian (Daedalus Enterprises, 2018)
Antibiotics have previously demonstrated anti-inflammatory properties, and they have been linked to therapeutic benefit in several pulmonary conditions that feature inflammation. Previous research suggests that these anti-inflammatory properties may be beneficial in the treatment of COPD. This review assesses the potential benefit of prophylactic, long-term, and low-dose antibiotic therapy in COPD, and whether any effects seen are anti-inflammatory in nature. Randomized, controlled trials comparing antibiotic therapy with placebo in subjects with stable COPD were evaluated. Twelve trials involving 3,784 participants and a range of antibiotics were included: azithromycin (6 studies, 1,972 participants), clarithromycin (1 study, 67 participants), erythromycin (3 studies, 254 participants), roxithromycin (1 study, 191 participants), and moxifloxacin (2 studies, 1,198 participants). In vitro, in vivo, and ex vivo experimental study designs exploring the mechanisms via which antibiotics may act in subjects with stable COPD were evaluated. Azithromycin and erythromycin showed the greatest effect in subjects with COPD, with evidence suggesting improvement in exacerbation-related outcomes and health status, as measured by the St George Respiratory Questionnaire. An increase in antibiotic resistance was reported in 2 studies. The macrolide class of antibiotics exhibited convincing anti-inflammatory properties with relevance to COPD, implicating several pathways as potential mechanisms of action. In conclusion, the therapeutic benefit of macrolide antibiotics in subjects with stable COPD is consistent with anti-inflammatory properties, and macrolides should be considered as a potential therapy in COPD. Safety concerns regarding antibiotic resistance need to be addressed before widespread use in clinical practice.